UPAYA PENINGKATAN KEPERCAYAAN DIRI SISWA SMP 5 MELALUI PROGRAM KAMPUS MENGAJAR 7: INCREASING STUDENTS' CONFIDENCE IN LEARNING MATHEMATICS THROUGH NUMERATION LITERACY CAMPUS TEACHING PROGRAM - Mahendra, Faisal Eka; Hasanudin, Hasanudin; Reawaruw, Marco Filip; Rahmadhani, Nailul Muna; Andini, Rya (KAMBIK: Journal of Mathematics Education, 2024)
This research aims to increase students' self-confidence in learning mathematics through the "numeracy literacy" program as part of the Teaching Campus initiative. The research method used was qualitative with a library study approach and direct observation at SMP Negeri 5 Sorong City. Initial observations show that interest in studying mathematics in grade 8 students is very low, as reflected in the low level of visits to the school library. The numeracy literacy program is carried out in groups, where students work on numeracy questions and then read the results of their work aloud and with the right intonation. The research results showed that after two weeks of implementing the program, there was a significant increase in self-confidence and interest in learning mathematics, as well as being able to read clearly and loudly, as well as the ability to speak in public. Apart from that, students' self-confidence in expressing opinions and speaking in public also increases. In conclusion, the numeracy literacy program is effective in increasing students' interest in learning mathematics and self-confidence. This program supports national education goals by making the nation's life smarter and realizing social justice through equitable and integrated education. The Teaching Campus Program, as part of Merdeka Belajar, plays an important role in assisting the teaching and learning process in schools and increasing student competency.